PENGARUH MODAL KERJA, PERTUMBUHAN PENJUALAN DAN LEVERAGE TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Perdagangan yang terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Sakfrasani, Fifi; Purwanto, Agus (Diponegoro Journal of Accounting, 2024)
This study aims to analyze the effect of working capital, sales growth and leverage on profitability and company value. The dependent variables in this study are profitability measured using ROE (Return On Equity) and company value measured by Tobin's Q ratio. The independent variables in this study are working capital measured using WCTO (Working Capital Turn Over), sales growth by calculating the increase in sales of a company from one period to the next, and leverage measured using the DER ratio (Debt to Equity Ratio). The population in this study is trading companies listed on the Indonesia Stock Exchange in 2020-2022. The total research sample used was 27 companies based on sampling techniques with purposive sampling. The data used in this study are secondary data obtained from the financial statements of companies listed on the Indonesia Stock Exchange and Bloomberg database. The data analysis method in the study used descriptive satatistic analysis and multiple linear regression.The statistical results of this study provide evidence that working capital has a positive and significant effect on profitability, leverage has a negative and significant effect on profitability, while sales growth variables do not have a significant effect on profitability. Profitability has a positive and significant effect on the value of the company. The variables of working capital, sales growth and leverage have a significant effect on the value of the company. The results of this study show that working capital, sales growth, leverage, and profitability simultaneously affect the value of the company.